Mother's Strategy in Forming Children's Defense in The Use of Gadgets in Digital Era to Form Reliable Children - Dina Mawaddatur Rohmah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
The rate of development of digital technology is increasing from time to time to bring a positive impact in all aspects of life. However, it cannot be denied also brings negative impacts. Technology crime is a threat to parents, especially mothers. How not, with all kinds of advanced technological developments, a family, especially mothers, plays the biggest role in escorting their children to become reliable children by forming children's self-defense. As a first and foremost educator, a mother is required to be a smart mother. Therefore, through this paper, the author seeks to initiate a surefire strategy for a mother to form a reliable child. The strategy is in the form of direction, training, assignment, habituation, escort, and role models. This is important for the child's learning process in an effort to instill values and character. Mother is not only required to teach her children to understand the media critically so as not to be consumed by hoaxes, but also to be wise in their use. Related to this, the authors conducted a library study (library research) to realize the strategy. So that it can be a solution for optimizing intelligence and character in the digital age and being able to maintain family institutions as miniature of superior society. Keywords: Strategy; Self defense; Gadget; Digital era